2014
DOI: 10.1016/j.jml.2014.05.004
|View full text |Cite
|
Sign up to set email alerts
|

Native ‘um’s elicit prediction of low-frequency referents, but non-native ‘um’s do not

Abstract: a b s t r a c tSpeech comprehension involves extensive use of prediction. Linguistic prediction may be guided by the semantics or syntax, but also by the performance characteristics of the speech signal, such as disfluency. Previous studies have shown that listeners, when presented with the filler uh, exhibit a disfluency bias for discourse-new or unknown referents, drawing inferences about the source of the disfluency. The goal of the present study is to study the contrast between native and non-native disflu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
54
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 68 publications
(59 citation statements)
references
References 60 publications
5
54
0
Order By: Relevance
“…The finding that listeners responded to the slightly slowed speech rate preceding cued codeswitches in some respects resembles findings that monolingual listeners are sensitive to naturalistic hesitation phenomena (Bosker, Quené, Sanders, & de Jong, 2014; Corley, MacGregor, & Donaldson, 2007) 8 . We think it quite reasonable that habitual codeswitchers could develop associations between hesitations and codeswitching much in the same way that monolinguals learn to associate hesitations with new information, for example (Arnold, Tanenhaus, Altmann, & Fagnano, 2004).…”
Section: Comprehension Studysupporting
confidence: 73%
“…The finding that listeners responded to the slightly slowed speech rate preceding cued codeswitches in some respects resembles findings that monolingual listeners are sensitive to naturalistic hesitation phenomena (Bosker, Quené, Sanders, & de Jong, 2014; Corley, MacGregor, & Donaldson, 2007) 8 . We think it quite reasonable that habitual codeswitchers could develop associations between hesitations and codeswitching much in the same way that monolinguals learn to associate hesitations with new information, for example (Arnold, Tanenhaus, Altmann, & Fagnano, 2004).…”
Section: Comprehension Studysupporting
confidence: 73%
“…For example, Arnold et al (2013) found that when encountering disfluent speech, listeners were more likely to expect a discourse-new referent. In line with this, Bosker et al (2014) showed that listeners were more likely to expect a low frequency as opposed to a high frequency word after a disfluency marker, though listeners adapted this expectation on the basis of the speaker the UM/UH ratio in American English based on the relatively recent Speed Dating Corpus (SDC; Jurafsky et al, 2009) and the older Switchboard corpus (Godfrey and Holliman, 1993) and obtained similar results, with women showing a greater UM/UH ratio than men in both corpora. Based on the Switchboard corpus, Acton (2011) also showed that this pattern persisted at the dialect-region level and when the gender of the hearer was taken into account (i.e.…”
Section: Introductionsupporting
confidence: 66%
“…Other studies have since shown the same effect in children as young as 2 years of age (Kidd, White, & Aslin, 2011;Orena & White, 2015;Owens & Graham, 2016;Owens, Thacker, & Graham, 2018;Thacker, Chambers, & Graham, 2018a, 2018b. Adult listeners have also been shown to be able to predict other types of complex referents, such as discourse-new (Arnold, Fagnano, & Tanenhaus, 2003;Arnold, Tanenhaus, Altmann, & Fagnano, 2004;Barr & Seyfeddinipur, 2010), compound (Watanabe, Hirose, Den, & Minematsu, 2008), and low-frequency referents (Bosker, Quené, Sanders, & De Jong, 2014a) upon hearing a disfluent filler uh.…”
mentioning
confidence: 86%
“…However, none of the eye-tracking studies cited in this paper report any order effect (neither positive nor negative; cf. Corley & Hartsuiker, 2011 for an overall order effect in reaction time data, but no interaction between order and delay), except for Bosker et al (2014a) and Thacker, Chambers, and Graham (2018b).…”
mentioning
confidence: 91%
See 1 more Smart Citation